Musical theatre for the female voice : the sensation, sound, and science, of singing - Aquilina, Shaun (Routledge, 2022)
"Female musical theatre singers face a unique and specific set of issues when approaching their craft, from negotiating the registers of their voice to enable them to belt, to vocal health challenges such as premenstrual voice syndrome. This is the only book that offers a full and detailed guide to tackling those issues and singing with full expression and technical excellence. Musical Theatre Singing for the Female Voice covers the origin of singing in musicals, from the bel canto style of 300 years ago through to the latest developments in high belting, in shows such as Wicked and Waitress. It offers the reader exercises and methods that have been used to train hundreds of singers at some of the UK's leading musical theatre training institutions and are underpinned by the latest academic research in journals on singing, psychology, and health. Every element of a singer's toolkit is covered from a female perspective, from breath and posture to character work and vocal health. This is an essential guidebook for female singers in musical theatre productions, either training at university or conservatory level or forging a career as professional triple-threat performers"--